2018
DOI: 10.1111/ced.13381
|View full text |Cite
|
Sign up to set email alerts
|

Association between circulating 25-hydroxyvitamin D levels and psoriasis, and correlation with disease severity: a meta-analysis

Abstract: This meta-analysis demonstrated that circulating 25(OH)D levels are lower in patients with psoriasis, and that a small but statistically significant negative correlation exists between 25(OH)D levels and psoriasis severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 21 publications
2
38
1
4
Order By: Relevance
“…There are evidences that psoriatic patients had significantly lower serum 25(OH)D concentrations than the healthy controls [16, 29, 30] and the prevalence of vitamin D deficiency (<20 ng/ml) was significantly higher in psoriatic patients than in the controls [14]. Our study showed a higher proportion of patients with vitamin D deficiency at baseline which is almost fivefold higher than the Thai population prevalence of 5.7% [31].…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…There are evidences that psoriatic patients had significantly lower serum 25(OH)D concentrations than the healthy controls [16, 29, 30] and the prevalence of vitamin D deficiency (<20 ng/ml) was significantly higher in psoriatic patients than in the controls [14]. Our study showed a higher proportion of patients with vitamin D deficiency at baseline which is almost fivefold higher than the Thai population prevalence of 5.7% [31].…”
Section: Discussionmentioning
confidence: 43%
“…Psoriasis is a multisystem inflammatory disorder with multiple associated comorbidities, such as psoriatic arthritis, obesity, metabolic syndrome, cardiovascular, and cerebrovascular diseases [2, 6, 11–13]. Several studies showed that circulating 25 hydroxyvitamin D (25(OH)D) levels were significantly lower among patients with psoriasis than healthy controls [1416]. Abnormal vitamin D metabolism may play a role in the pathogenesis of psoriasis [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, low 25(OH)D levels can either represent the cause or consequence of psoriasis, resulting from lack of sun exposure, from frequent use of drugs that interfere with 25(OH)D metabolism (such as gluco-corticoids and immunosuppressive agents), or from low 25(OH)D intake. [ 16 , 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, those affected by long-time psoriasis, and not undergoing phototherapy, could possibly be more prone to vitamin D reduced serum levels. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Orgaz‐Molina et al and Hassab‐El‐Naby et al reported that there was no relationship between 25(OH)D 3 levels and Psoriasis Area Severity Index (PASI) 7,8 . However, studies by Bergler‐Czop et al , Tajjour et al , Lee et al , and Ingram et al reported a significant negative correlation between serum levels of 25(OH)D 3 with PASI score 9–12 …”
Section: Introductionmentioning
confidence: 99%